2005
DOI: 10.1007/s10554-005-9039-6
|View full text |Cite
|
Sign up to set email alerts
|

From atherosclerotic coronary ectasia to aneurysm: a case report and literature review

Abstract: In contrast to Kawasaki syndrome the formation of coronary aneurysms caused by atherosclerosis has hardly been demonstrated. We report on a 56-year old patient, admitted to our hospital for cardiovascular evaluation before carotid surgery. He had no anginal pain, but a history of coronary artery disease with previous anterior myocardial infarction. Angiography revealed a collateralized LAD occlusion. Myocardial scintigraphy only demonstrated fixed perfusion defects. Surprisingly, MR imaging revealed large coro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
9
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Pre-existing CAAs of the native vessels have a propensity to enlarge in size following coronary artery bypass surgery. This is especially common in ectatic arteries [4]. In such situation, surgical resection of the aneurysm might not be an option and percutaneous treatment is a feasible alternative.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pre-existing CAAs of the native vessels have a propensity to enlarge in size following coronary artery bypass surgery. This is especially common in ectatic arteries [4]. In such situation, surgical resection of the aneurysm might not be an option and percutaneous treatment is a feasible alternative.…”
Section: Discussionmentioning
confidence: 99%
“…The effectiveness and long term outcomes to this technique will have to be studied with serial CT angiography. Primary criteria to assess the outcomes include [1] any potential recanalization with the coil embolization technique along with the regrowth of the sac, [2] intra-aneurysmal thrombosis formation, [3] thrombogenic issue with a stent graft, and [4] any potential luminal area reduction by tissue growth.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast giant aneurysms progress and become obstructive lesions due to thrombus formation. Enlargement of a coronary aneurysm after the acute phase in Kawasaki disease is an extremely rare phenomenon [1][2][3]. Giant coronary aneurysms are sometimes misdiagnosed as cardiac tumors when they are filled with thrombus [4].…”
Section: Introductionmentioning
confidence: 99%
“…Plehn et al preferred to use the term coronary artery aneurysm for segmental ectasia, reserving the term ectasia for diffuse vessel involvement. 12 They classified aneurysms as small (< 5 mm), medium (5-8 mm), or giant (e" 8 mm). In addition, coronary artery aneurysm has been classified as the fusiform or saccular type based on the anatomic shape of the ecstatic segment.…”
mentioning
confidence: 99%
“…Plehn et al reported a patient who presented with ectatic lesions that rapidly progressed to aneurysmatic lesions within 3 years. 12 The patient was treated with aneurysm ligation and coronary artery bypass grafting (CABG). A coronary aneurysm was diagnosed if the internal lumen diameter was >4.0 mm.…”
mentioning
confidence: 99%